Modelo para postagens de notícias com enfoque na qualidade da informação - Maia, Maria Aniolly Queiroz (2022)
The news portals are environments that provide information very relevant to society; therefore, they are expected to be useful to its users. However, this task is quite complex, since it encompasses objective and subjective aspects that are hardly measured, in order to present the best wayto guarantee the quality of this information. Thus, this article aims to raise, analyze and propose a model of information quality attributes, with a view to improving the quality of what is posted in these informational environments and, thus, collaborating with the production of quality information, according to the conceptual protection of information communication.